2016
DOI: 10.1007/s12664-016-0622-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-variceal upper gastrointestinal bleeding in cirrhotic patients in Nile Delta

Abstract: Non-variceal bleeding in cirrhosis was not frequent, and sources included peptic ulcer, portal hypertensive gastropathy, and erosive disease of the stomach and duodenum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…This may be explained by the fact that viral liver disease is much more prevalent in our younger population. Our results are somewhat compatible to four studies: Romcea et al 13 , Svoboda et al 19 , GonzálezGonzález et al 20 , and Gabr et al 16 (56.76, 56.9, 56.5 and 58.57 years old, respectively). The vast majority (75%) of cases of cirrhosis were due to HCV, which was comparable to some 16 , however it contradicts the many western studies in which alcohol is the most common cause of cirrhosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This may be explained by the fact that viral liver disease is much more prevalent in our younger population. Our results are somewhat compatible to four studies: Romcea et al 13 , Svoboda et al 19 , GonzálezGonzález et al 20 , and Gabr et al 16 (56.76, 56.9, 56.5 and 58.57 years old, respectively). The vast majority (75%) of cases of cirrhosis were due to HCV, which was comparable to some 16 , however it contradicts the many western studies in which alcohol is the most common cause of cirrhosis.…”
Section: Discussionsupporting
confidence: 93%
“…The demographic analysis of our study revealed that AUGIB is much more common in male cirrhotic patients as compared to female patients (62.4% versus 37.6%, p<0.0001) and this is compatible with many other studies. 13,14,15,16 Mean age at presentation in some studies is around 65-70 years. 17,18 In contrast to these studies mean age of cirrhotic patients presenting with AUGIB in our study was 50.15 years.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality had no significant correlation to source of bleeding variceal or non variceal, rebleeding, intervention during endoscopy, grade of EV, or PHG, grade of encephalopathy, presence of focal lesion, portal vein patency, or use of NSAID's. [11]. All these studies say that the males are more at risk of upper GI bleeding than females.…”
Section: Resultsmentioning
confidence: 99%
“…Acute upper gastrointestinal bleeding (UGIB) is the most common gastroenterological emergency in patients with cirrhosis and correlated with significant morbidity and mortality [1,2]. Acute variceal bleeding (AVB) is the leading cause of UGIB in cirrhosis and account for up to 70% of all cases [3,4], while non variceal bleeding (NVB) is a considerable cause of UGIB and responsible for the remaining cases, with the most frequent being peptic ulcer disease (PUD) [5]. In recent years significant amelioration in the therapeutic management of UGIB and improvement of hemostatic therapies resulted in a reduction of mortality and improvement of prognosis whether the cause is variceal [6,7] or non-variceal [7,8] Observational studies have demonstrated the higher mortality rate among patients with a bleeding Peptic ulcer with cirrhosis than in those without liver disease [9,10].…”
Section: Introductionmentioning
confidence: 99%